Islet organoids: a new hope for islet transplantation in diabetes - Yu, Xuemei; Liu, Chengkong; Kuang, Zheng; Song, Siyuan; Tian, Limin; Wang, Yi (Frontiers in Immunology, 2025)
Diabetes mellitus, including Type 1 diabetes (T1D) and advanced Type 2 diabetes (T2D), remains a major global health challenge due to the destruction or dysfunction of insulin-producing β-cells. Islet transplantation offers a promising therapeutic strategy. However, it is limited by organ shortage globally and other risk factors. Recent advancements in organoid technology provide transformative solutions for islet regeneration. This review summarized three groundbreaking approaches: islet organoids differentiated from Procr+ pancreatic progenitor cells, chemically induced pluripotent stem cells (CiPSCs), and endoderm stem cells (EnSCs). Procr+ cells exhibit multipotency and potential for in vivo activation, offering a scalable and non-invasive strategy for β-cell regeneration. CiPSCs, reprogrammed via small molecules, enable personalized islet therapies with promising clinical outcomes, as demonstrated in T1D patients. EnSC-derived islets (E-islets) offer high differentiation efficiency and therapeutic efficacy, particularly for T2D patients with residual β-cell function. While each approach addresses specific challenges in islet transplantation, further research is needed to optimize scalability, immune compatibility, and long-term functionality. This review highlights the potential of organoid-based technologies to revolutionize diabetes treatment and pave the way for personalized, curative therapies.